Liver failure associated with autoimmune hepatitis in the presence of active infections by Epstein‒Barr virus and cytomegalovirus: a case report - Santos, Damiao; Alves Pinto, Marcelo; Leal Corrêa, Christiane; Filgueiras Pacheco-Moreira, Lúcio; Salete de Paula, Vanessa (Estação Científica, 2024)
Background: Liver failure occurs due to extensive hepatocellular damage and may be induced by several etiologies, including autoimmunity and hepatotropic and non-hepatotropic viruses. Cytomegalovirus (CMV) and Epstein‒Barr virus (EBV) are viruses from the Herpesviridae family that usually cause latent infections but may trigger severe liver disease and dysfunction. Case presentation: Herein, we report a case of a 48-year-old female patient with jaundice, coagulopathy, encephalopathy, hyperbilirubinemia, and autoimmunity marker. The patient was referred to a public hospital in Rio de Janeiro, Brazil, and underwent a liver transplant. Serological and molecular diagnosis showed active infections by EBV and CMV. Conclusions: The presence of latent or active infection by EBV or CMV needs to be investigated in patients with liver failure of unknown etiology, which might trigger severe autoimmune hepatitis.